2004
DOI: 10.1002/cncr.20349
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography for unexplained elevation of serum squamous cell carcinoma antigen levels during follow‐up for patients with cervical malignancies

Abstract: BACKGROUND During follow‐up for patients with cervical carcinoma, elevation of serum squamous cell carcinoma antigen (SCC‐Ag) levels in the absence of detectable recurrent lesions presents a diagnostic and therapeutic challenge. In the current prospective study, the authors evaluated the use of fluorine‐18‐labeled fluoro‐2‐deoxy‐D‐glucose (FDG) positron emission tomography (PET) to detect disease recurrence in this setting. METHODS Women with cervical carcinoma who experienced complete responses to primary tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 21 publications
0
50
1
8
Order By: Relevance
“…Previous studies have reported that increasing serum SCCA can precede the clinical diagnosis of relapse in 46-92% of cases (19)(20)(21). However, it is still a matter of debate whether serum SCCA assay may represent a prognostic variable and be useful for earlier diagnosis of relapse (22,23). Most reports found CYFRA 21-1 to be a less sensitive serum tumor marker for squamous cell cervical cancer than SCCA (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that increasing serum SCCA can precede the clinical diagnosis of relapse in 46-92% of cases (19)(20)(21). However, it is still a matter of debate whether serum SCCA assay may represent a prognostic variable and be useful for earlier diagnosis of relapse (22,23). Most reports found CYFRA 21-1 to be a less sensitive serum tumor marker for squamous cell cervical cancer than SCCA (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, further investigation is needed to determine whether SCC monitoring is really useful or not in clinical practice. It has been reported in a small series of patients with recurrent cervical cancer that the addition of positron emission tomography to SCC monitoring significantly increased overall survival compared with a historical group of patients who had elevated SCC concentrations as a first sign of recurrent disease (443 ). …”
Section: Use Of Scc In Monitoring Response To Treatment and Early Detmentioning
confidence: 98%
“…Several authors have investigated the usefulness of PET for postoperative or post-therapy surveillance of patients with cervical cancer and found that the sensitivity, specificity, and accuracy were 86-100%, 60-94%, and 70-97%, respectively (Table 4) [12][13][14][15][16][17][18][19]. These studies revealed that false-negative cases included local recurrence in the retrovesical region, pelvic recurrence, lung metastasis, peritoneal dissemination, pelvic LN metastasis, and para-aortic LN metastasis, whereas false-positive cases were due to inflammatory lesions, physiological uptake, and postoperative change.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies of FDG-PET [12][13][14][15][16][17][18][19] and only two reports of integrated FDG-PET/CT [20,21] describing their usefulness for the diagnosis of recurrent uterine cervical cancers. Chung et al [20] and Sironi et al [21] discussed the diagnostic accuracy of PET/CT, but did not compare PET/CT interpretation with PET-alone interpretation.…”
Section: Introductionmentioning
confidence: 99%